[Cover letter to S. Chilcote from A. J. Stevens introducing a letter from the National Korean Grocers Association] - Stevens, Arthur J (Tufts Archival Research Center, 2007)
Missing Attachments; Cover letter to Samuel Chilcote from Arthur J Stevens introducing a letter from the National Korean Grocers Association (KAGRO). Indicates that KAGRO will be an important ally to the tobacco industry. Ask that a Tobacco Institute representative contact KAGRO in order to enlist their help as soon as possible.